2018
DOI: 10.1158/1541-7786.mcr-18-0055
|View full text |Cite
|
Sign up to set email alerts
|

Ferroptosis-Induced Endoplasmic Reticulum Stress: Cross-talk between Ferroptosis and Apoptosis

Abstract: Since its discovery in 2012, ferroptosis has been well characterized by the accumulation of lipid peroxides due to the failure of glutathione-dependent antioxidant defenses. It is known as an iron-dependent form of programmed cell death, which is distinct from other forms of cell death such as apoptosis and necrosis. Nonetheless, little is known about the ferroptotic agent-induced endoplasmic reticulum (ER) stress response and its role in cell death. Recent studies reveal that the ferroptotic agent-induced ER … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
151
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 276 publications
(169 citation statements)
references
References 47 publications
4
151
0
Order By: Relevance
“…Along with the evidence that miR-132/212 was consistently downregulated in AD [24], it is reasonable to speculate that miR-212 may act like a bridge between TBI and neurodegenerative diseases. Moreover, there is a consensus that crosstalk widely exists between ferroptosis and other forms of regulated cell death [53,[63][64][65][66], and emerging evidence indicates that miR-212 may prevent neuron death by inhibiting other target genes, like Sirt2 [67] or participating in other pathways, like autophagy [65,66] or apoptosis [63]. Further studies are urgently required to identify whether miR-212-5p is involved in any other pathologic process of TBI.…”
Section: Discussionmentioning
confidence: 99%
“…Along with the evidence that miR-132/212 was consistently downregulated in AD [24], it is reasonable to speculate that miR-212 may act like a bridge between TBI and neurodegenerative diseases. Moreover, there is a consensus that crosstalk widely exists between ferroptosis and other forms of regulated cell death [53,[63][64][65][66], and emerging evidence indicates that miR-212 may prevent neuron death by inhibiting other target genes, like Sirt2 [67] or participating in other pathways, like autophagy [65,66] or apoptosis [63]. Further studies are urgently required to identify whether miR-212-5p is involved in any other pathologic process of TBI.…”
Section: Discussionmentioning
confidence: 99%
“…Activating transcription factor 4 (ATF4) is an essential mediator of endoplasmic reticulum (ER) stress (Bi et al, 2005). Besides ER stress damages, diverse microenvironmental stimuli, including exposure to ferroptosis inducers, can also induce its elevation (Lee, Lee, Choudry, Bartlett, & Lee, 2018). ATF4 has recently been demonstrated to act as a negative regulator in ferroptosis (Chen, Fan et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Ferroptosis is considered distinct from other forms of cell death such as necrosis and apoptosis. Nevertheless, several studies have reported a cross-talk between ferroptosis and apoptosis, especially related to ER-stress 49,50 . Thus, to investigate the alteration of ferroptosis by iron overload, we assessed ferroptotic markers, such as the levels of GPX activity and lipid peroxidation, in hippocampal tissues from HFe-fed WT and Prx5 −/− mice with or without NAC.…”
Section: Discussionmentioning
confidence: 99%